Porocarcinoma: an epidemiological, clinical, and dermoscopic 20‐year study. (28th February 2022) - De Giorgi, Vincenzo; Silvestri, Flavia; Savarese, Imma; Venturi, Federico; Scarfì, Federica; Trane, Luciana; Bellerba, Federica; Zuccaro, Biancamaria; Maio, Vincenza; Massi, Daniela; Gandini, Sara
Abstract: Background: Porocarcinoma (PC) is a rare cutaneous adnexal tumor with a variable metastatic potential. Given the paucity of data, guidelines and specific recommendations for PC are not yet well‐established. In this study, we evaluate the disease‐specific characteristics and outcome of this rare and often underestimated tumor. Materials and method: A retrospective study of the epidemiological, clinical, and dermoscopic characteristics among cases of histopathologically diagnosed PC, collected from the database of two skin cancer clinics in Italy (Firenze, Pistoia) from 2000 to 2020, was conducted. Results: Among the 52 patients with 53 tumors, 31 were men (59.6%) and 21 were women (40.4%) with an age range of 49–96 years (median age 82 years). The most common locations were the head/neck region in men (34% in men vs. 17% in women) and the lower limb in women (17% in women vs. 9% in men). Forty‐eight cases (91%) underwent local excision. Of these patients, two (4%) experienced local recurrence, and one (2%) developed a second PC on a different anatomical site 1 month after the primary tumor's excision. Lymph node metastases were present in three cases (6%). Two of them have been treated surgically with adjuvant radiotherapy (both are disease‐free after a 2‐year follow‐up period), whereas the third case developed visceral metastases followed by PC‐related death. Conclusions: This study, with 52 patients with 53 tumors covering a follow‐up period of more than 5 years, shows a less aggressive behavior of PC with 4% local recurrence, 6% nodal metastases, and 2% mortality.